A Broker's Perspective: Managing Permutations of International Risks - Clark, Peter T. (Assurances, 1990)
This report develops the concept that the design of a multinational global corporate insurance program requires proper planning and understanding of local laws and customs. Taking a long-term, global view of corporate risk management objectives with proper evaluation and implementation of the risk finance and risk control mechanisms sets the foundation to transfer risk economically, and guarantees that funds will be available to pay losses when they occur. Understanding how to use before tax dollars to fund for losses and transfer risk is an intricate process involving local admitted coverages and reinsurance. This report attempts to shed some light on this process, and it makes some suggestions on how to minimize the effects losses may have on corporate income taxes as well as ways to manage global risks that will stand the test of time.